BCL9 provides multi-cellular communication properties in colorectal cancer by interacting with paraspeckle proteins - Meng Jiang; Yue Kang; Tomasz Sewastianik; Jiao Wang; Helen Tanton; Keith Alder; Peter Dennis; Yu Xin; Zhongqiu Wang; Ruiyang Liu; Mengyun Zhang; Ying Huang; et al. (Nature Communications, 2020)
BCL9 is an activator of oncogenic Wnt/β-catenin. Here, the authors show a β-catenin independent function of BCL9 in a subtype of colorectal cancers, where it interacts with paraspeckle proteins to enhance the mRNA stability of calcium signalling and neural associated genes to promote communication with tumour cells and its microenvironment.